Motivasi Kontrol Gula Darah Pasien DMT2 dengan Menggunakan Website Peer Tutoring (Sweetech-DM) di Puskesmas Suwawa Kabupaten Bone Bolango - Kattang, Giselia; Zainuddin, Zainuddin; Yusuf, Nurayun R; Purwanto, Erwin (Yayasan Mandar Indonesia, 2025)
This study explores the Sweetech-DM website as a peer tutoring-based educational platform aimed at enhancing blood glucose control motivation among patients with Type 2 Diabetes Mellitus. Sweetech-DM provides information and educational videos created by fellow patients. The objective of this research is to examine the website's impact on patients’ motivation in managing their diabetes. A quantitative approach with a descriptive survey design was employed. The study population consisted of 262 individuals, with 18 respondents selected through purposive sampling. The Treatment Self-Regulation Questionnaire (TSRQ) was used as the instrument to measure motivation levels. The results indicate an increase in motivation for blood glucose control after using Sweetech-DM. Peer tutoring was found to effectively support patients in becoming more motivated to manage their condition independently. Digital educational media that incorporates peer support is considered effective. Sweetech-DM shows potential as a sustainable educational solution for diabetes management.